2020
DOI: 10.1371/journal.pone.0231427
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of lenvatinib for patients with unresectable hepatocellular carcinoma based on the middle-term outcome

Abstract: This study sought to clarify the usefulness of lenvatinib for patients with unresectable hepatocellular carcinoma (HCC). Methods The subjects were 69 patients with HCC receiving lenvatinib; the median age was 73 years, and 14 and 67 patients had been previously treated with regorafenib and/or sorafenib and therapies without molecular-targeted agents, respectively. Therapeutic efficacy was evaluated using contrast-enhanced CT images obtained 4-8 weeks after the start of lenvatinib and the middle-term outcome us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…We have previously reported that hepatic encephalopathy developed in approximately 11% of patients receiving lenvatinib for unresectable HCC during an observation period of 48 weeks. 19 The therapeutic efficacy of rifaximin in patients receiving molecular targeted drugs needs to be investigated in future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that hepatic encephalopathy developed in approximately 11% of patients receiving lenvatinib for unresectable HCC during an observation period of 48 weeks. 19 The therapeutic efficacy of rifaximin in patients receiving molecular targeted drugs needs to be investigated in future.…”
Section: Discussionmentioning
confidence: 99%
“…Overt hepatic encephalopathy, however, was reported to be induced by treatment for HCC, especially during treatment with molecular targeted drugs. We have previously reported that hepatic encephalopathy developed in approximately 11% of patients receiving lenvatinib for unresectable HCC during an observation period of 48 weeks 19 . The therapeutic efficacy of rifaximin in patients receiving molecular targeted drugs needs to be investigated in future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a sensitivity analysis was performed by altering the models. As entered variables of Models 1, 2, 3, and 4, age, hypothyroidism grade, sex, Child-Pugh score, hypoalbuminemia grade, TNM stage, and BCLC stage were selected based on previous reports on clinical importance to outcomes [ 19 , 21 , 24 , 38 , 39 ]. We consider that the number of variables that could be entered into the model was four at the maximum because of the small sample size.…”
Section: Methodsmentioning
confidence: 99%
“…This, together with the large volume of administration of chemotherapeutic agents and their unspecific mechanism of action, causes severe side effects [ 15 ]. Therefore, the novel chemotherapeutic agents or strategies are urgently needed to treat HCC patients with minimal or tolerable side effects [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of biodegradable nanomaterials has received impressive attention. Ploy (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), a biodegradable biopolymer with a low glass transition temperature and a hard texture, which is produced by using starch as raw material and fermentation engineering technology [ 16 , 17 ]. PHBV has a variety of advantages such as favorable biocompatibility and low manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%